Kepemimpinan Kepala Madrasah dalam Menciptakan Budaya Belajar Yang Inklusif Bagi Siswa Di MTs NW Senyiur - M. Saipul Watoni; Romi Oriza; Muhamad Yusril (Al-Gafari : Manajemen dan Pendidikan, 2023)
The principal of the madrasah as a leader of institution education must be responsible for answers to all madrasa activities. He has authority and responsibility answer full for organizing all activity education in the madrasa environment he leads. Goals the study is to know the role and strategy of the madrasa head in creating culture-inclusive learning for students at MTs NW Senyiur. The research methods used are qualitative descriptive. Data collection techniques use technique interviews, observations, and documentation. Data is analyzed using data reduction, data presentation, and withdrawal conclusion. Research results show that the head of the madrasa runs his role in creating culture-inclusive learning for students that is as an educator, manager, administrator, supervisor, leader, innovator, and motivator through application values. Conclusions of study These are 1) students' attitude reception themselves and be accepted into the madrasa, 2) students have a sense of trust in themselves at the madrasa, 3) students grow to become characters who are caring, empathetic, and mutual help, 4) students own ability for express opinion in a way constructive 5) students trained and have ability cooperate and respect.